Mouse models of myeloproliferative neoplasms: JAK of all grades - Juan Li; David G. Kent; Edwin Chen; Anthony R. Green (The Company of Biologists, 2011)
In 2005, several groups identified a single gain-of-function point mutation in the JAK2 kinase that was present in the majority of patients with myeloproliferative neoplasms (MPNs). Since this discovery, much effort has been dedicated to understanding the molecular consequences of the JAK2V617F mutation in the haematopoietic system. Three waves of mouse models have been produced recently (bone marrow transplantation, transgenic and targeted knock-in), which have facilitated the understanding of the molecular pathogenesis of JAK2V617F-positive MPNs, providing potential platforms for designing and validating novel therapies in humans. This Commentary briefly summarises the first two types of mouse models and then focuses on the more recently generated knock-in models.